# X and Y Intercepts.

## Presentation on theme: "X and Y Intercepts."— Presentation transcript:

X and Y Intercepts

The y intercept is the point at which the graph of an equation crosses the y axis.
y = 2x + 3 y (0,3) x

The y intercept is the point at which the graph of an equation crosses the y axis.
y = 2x + 3 y Notice that the x value is zero. (0,3) x

The x intercept is the point at which the graph of an equation crosses the x axis.
y = 2x + 3 y (-3/2 ,0) x

The x intercept is the point at which the graph of an equation crosses the x axis.
y = 2x + 3 y (-3/2 ,0) x Notice that the y value is zero.

Example #1 Find the y and x intercepts. Then graph the line.
y = 2x + 6

Example #1 Find the y and x intercepts. Then graph the line.
y = 2x + 6 y intercept y = 2(0) + 6 y = 6 (0,6)

Example #1 Find the y and x intercepts. Then graph the line.
y = 2x + 6 y intercept y = 2(0) + 6 y = 6 (0,6) x intercept 0 = 2x + 6 x = -3 (-3,0)

Example #1 Find the y and x intercepts. Then graph the line.
y = 2x + 6 y (0,6) (-3,0) x

Example #1 Find the y and x intercepts. Then graph the line.
y = 2x + 6 y (0,6) (-3,0) x

Example #2 Find the y and x intercepts. Then graph the line.
y = 3x + 12

Example #2 Find the y and x intercepts. Then graph the line.
y = 3x + 12 y intercept y = 3(0) y = 12 (0,12)

Example #2 Find the y and x intercepts. Then graph the line.
y = 3x + 12 y intercept y = 3(0) y = 12 (0,12) x intercept 0 = 3x x = -4 (-4,0)

Example #2 Find the y and x intercepts. Then graph the line.
y = 3x + 12 y (0,12) (-4,0) x

Example #2 Find the y and x intercepts. Then graph the line.
y = 3x + 12 y (0,12) (-4,0) x

Practice Time

For each function, find the x and y intercepts. Then graph the line.

1) y = ½ x + 4

1) y = ½ x + 4 y intercept y = ½ (0) + 4 y = 4 (0,4)
x intercept 0 = ½ x + 4 x = -8 (-8,0)

1) y = ½ x + 4 y (0,4) (-8,0) x

2) y = -2 x + 8

y intercept y = -2 (0) + 8 y = 8 (0,8)
2) y = -2 x + 8 y intercept y = -2 (0) + 8 y = 8 (0,8) x intercept 0 = -2 x + 8 x = 4 (4,0)

2) y = -2 x + 8 y (0,8) (4,0) x

3) y = -3x - 4

3) y = -3x - 4 y intercept y = -3 (0) - 4 y = -4 (0,-4)
x intercept 0 = -3 x - 4 x = -4/3 (-4/3,0)

3) y = -3x - 4 y (-4/3,0) x (0,-4)

4) y = 8x - 2

y intercept y = 8 (0) - 2 y = -2 (0,-2)
4) y = 8x - 2 y intercept y = 8 (0) - 2 y = -2 (0,-2) x intercept 0 = 8 x - 2 x = 1/4 (1/4,0)

4) y = 8x - 2 y (1/4,0) x (0,-2)

5) 2x + 3y = 6

5) 2x + 3y = 6 y intercept 2(0) + 3y = 6 y = 2 (0,2)
x intercept 2x + 3(0) = 6 x = 3 (3,0)

5) 2x + 3y = 6 y (0,2) (3,0) x

6) 5x + 2y = 10

6) 5x + 2y = 10 y intercept 5(0) + 2y = 10 y = 5 (0,5)
x intercept 5x + 2(0) = 10 x = 2 (2,0)

6) 5x + 2y = 10 y (0,5) (2,0) x

7) -3x + 5y = 9

7) -3x + 5y = 9 y intercept -3(0) + 5y = 9 y = 9/5 (0,9/5)
x intercept -3x + 5(0) = 9 x = -3 (-3,0)

7) -3x + 5y = 9 y (0,9/5) (-3,0) x

8) -2x - 3y = 10

8) -2x - 3y = 10 y intercept -2(0) - 3y = 10 y = -10/3 (0,-10/3)
x intercept -2x - 3(0) = 10 x = -5 (-5,0)

8) -2x - 3y = 10 y (-5,0) (0,-10/3)

Similar presentations